ChemInform Abstract: The Hexacyanodiborane(6) Dianion [B2(CN)6]2‐. Issue 47 (November 2015) - Landmann, Johannes; Sprenger, Jan A. P.; Hailmann, Michael; Bernhardt‐Pitchougina, Vera; Willner, Helge; Ignat'ev, Nikolai; Bernhardt, Eduard; Finze, Maik
Abstract: Various reaction routes leading to the homoleptic dianion [B2 (CN)6 ] 2‐ are presented together with spectroscopic data and the formation mechamisms are discussed.